Restoring High Vaccine Coverage in Brazil: Successes and Challenges - Fernandes, Eder Gatti (2023)
Facing the decline in vaccine coverage observed since 2016, the new Brazilian government committed to reversing this scenario. To achieve this, the Federal Government launched the National Vaccination Movement and the 'Health with Science' platform to combat vaccine misinformation, promoted Microplanning, providing tools for decision-making at the territorial level, allocated 30 million dollars to states and municipalities to implement innovative vaccination strategies, standardized the rules of the information systems for the registration of vaccine doses, and directed data to the National Health Data Network (RNDS). Reversing the declining trend of vaccination coverage in Brazil is challenging, but within just one year, it is possible to observe significant results from governmental actions. Out of the eight recommended vaccines by the age of one, seven showed an increase in vaccination coverage in 2023 compared to 2022: Most states showed improvements in vaccination coverage. Many challenges persist in advancing the vaccination agenda. However, there are reasons to celebrate the reversal of the declining trend in coverage of several vaccines in this first year of government and the increase in the number of municipalities that have fully achieved the vaccination coverage target. The National Vaccination Movement, with public opinion awareness, the resumption of regionalized communication campaigns, localized micro-planning actions including extramural vaccination strategies, and the integration of information systems, has been decisive in strengthening work in the territories and thus restoring a culture of immunization, a source of pride in the country and internationally recognized, throughout the 50 years of the National Immunization Program